Rolos de impacto de transportadores de correias: avaliação do desgaste em campo e em laboratório - Loureiro, Igor Emanoel Espindola (2024)
This master’s thesis aims to quantify and understand the reasons that led to the replacement of the rollers and characterize the rubber coating of the impact idler rollers based on this. By analyzing data on roller idler replacement, almost 90% of the reasons for replacing impact and load idler rollers are: noise, wear and seizure, in that order for both. Noise replacement (possibly from bearing damage) is more significant for load idler rollers and wear is more significant for impact idler rollers. The return idler rollers presented another hierarchy, being: wear, noise and standardization, in that order. To characterize the idler rollers used, three idler rollers (without failure) and one idler roller that had already failed were initially analyzed. In these four idler rollers from the same manufacturer, the profile of the radius deviations caused by wear, the hardness profile and their wear mechanisms were measured. It was observed that the radius deviation profile follows the hardness profile, só in regions where there was more radius deviation, higher hardnesses were measured. It was also observed that the idler rollers that had not failed presented Schallamach waves as the predominant wear mechanisms, while in the failed roll it was microgrooving and/or microcutting, presenting more severe wear. Subsequently, tests were carried out to evaluate the energy absorption capacity and wear resistance. Five types of samples were used: new idler roller (RN), new idler roller thermally aged for 70 hours (RN-ET70), new idler roller thermally aged for 240 hours (RN-ET240), used idler roller from the central region (RUD Centro) and idler roller used from the edge region (RUD Borda). Therefore, two types of abrasion tests were carried out, a modified rubber wheel test with a locked sample and a pin-drum test, and a compression test to determine the modulus of resilience and modulus of elasticity. The wear results obtained in the pin-drum test did not present a coefficient of determination close to 1 with hardness, modulus of resilience and modulus of elasticity. While the modified rubber wheel test with locked sample presented a coefficient of determination close to 1 with the resilience modulus, elasticity modulus, contact area and contact pressure when disregarding the RN. Thermal aging reduced the wear resistance of the rubber, both in the field and in the oven, for both tests. When considering only RN samples and varying the test force, a coefficient of determination close to 1 was observed between the wear rates with force, the maximum Hertz contact pressure and the friction density energy.